2014
DOI: 10.1186/1476-069x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Maternal blood manganese level and birth weight: a MOCEH birth cohort study

Abstract: BackgroundManganese (Mn) is an essential trace element for humans and animals, but excess intake of Mn can lead to adverse developmental outcome. Few studies have investigated the effects of deficiency or excess of Mn on the human foetus. In this study, we assessed the quantitative relationship between maternal blood Mn and birth weight of a newborn.MethodsWe performed analysis on 331 full-term, live birth singleton mother-infant pairs enrolled from July 2007 to December 2009 in the Mother and Children’s Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 24 publications
6
39
0
1
Order By: Relevance
“…In contrast, 75.7% of women exceeded the reference levels for Mn [49][50][51]. The relatively high levels of Mn in the study population were similar to those previously reported in postpartum mothers form Norway [28], in mothers before delivery in South African coastal communities (from part "Rural 2") [54], in pregnant woman from Southwest Quebec [46], in the Mother and Children's Environmental Health birth cohort study in Seoul, in Cheonan, and Ulsan in the Republic of Korea at delivery [30] and in pregnant women from Costa Rica [25]. The concentrations of essential elements at 6 weeks postpartum may have changed according to physiological and metabolic changes during pregnancy and during the postpartum/lactation period, as was demonstrated by Hansen et al who found that concentrations of Mn, Se, Zn and As increased postpartum [28].…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast, 75.7% of women exceeded the reference levels for Mn [49][50][51]. The relatively high levels of Mn in the study population were similar to those previously reported in postpartum mothers form Norway [28], in mothers before delivery in South African coastal communities (from part "Rural 2") [54], in pregnant woman from Southwest Quebec [46], in the Mother and Children's Environmental Health birth cohort study in Seoul, in Cheonan, and Ulsan in the Republic of Korea at delivery [30] and in pregnant women from Costa Rica [25]. The concentrations of essential elements at 6 weeks postpartum may have changed according to physiological and metabolic changes during pregnancy and during the postpartum/lactation period, as was demonstrated by Hansen et al who found that concentrations of Mn, Se, Zn and As increased postpartum [28].…”
Section: Resultssupporting
confidence: 70%
“…The mean age of the mothers was 29 years, the mean pre-pregnancy BMI was 23.1 kg/m 2 , the mean estimated gestational length was 39.7 weeks, 50% of women have at least university education, 53.8% of babies were males, and the mean birth length for all babies was 51.4 cm. The mean birth weight of the babies in our study was comparable with those reported elsewhere [23,30,35,38,45,46]. A total of 3.4% of the new-borns were below the criterion for "low birth weight" of 2,500 g [17], and 0.2% of new-borns were below 1,500 g, considered as a "very low birth weight" [47].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A number of studies have examined the effects of prenatal Mn exposure on birth outcomes in humans (Table S1) (Chen et al 2014; Eum et al 2014; Guan et al 2013; Osada et al 2002; Takser et al 2004; Vigeh et al 2008; Xu et al 2011; Yu and Cao 2013; Zota et al 2009). Cross-sectional studies in Oklahoma ( n = 470 term newborns), China ( n = 172 preterm and term infants), and Korea ( n = 331 term newborns) have reported nonlinear associations between maternal blood Mn concentrations at delivery (medians = 22, 53.8, and 21.5 μg/L, respectively) and birth weight (Chen et al 2014; Eum et al 2014; Zota et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Він також бере участь у функ-ціонуванні антиоксидантних ферментів, таких як супе-роксиддисмутаза, та активує глікозилтрансферазу, яка має важливе значення для розвитку кісткової та сполучної тканини [8]. Деякі дослідження показують взаємозв'язок між рівнем марганцю у крові матері та масою тіла при народженні дитини [9]. Отже, плацента є органом, який відіграє важливу роль як депо есенціальних МЕ.…”
Section: Discussionunclassified